2002
DOI: 10.1177/15648265020234s213
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Styles of Feeding and Child Acceptance of Food in Rural Viet Nam

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
12

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 12 publications
2
21
0
12
Order By: Relevance
“…It was found that almost all existing instruments emphasized on parental feeding activities or psychomotor activities that focus on the activities or strategies that parents use to manage how much, when and what children eat such as on parental use of control in feeding. [15][16][17][18] There was a lack of construct involved in cognitive activities that reflected acquiring and gathering information and making judgment and decision. Although Birch, et.al, (2001) and Jansen, et.al., (2012) state that the feeding behaviors of parents are attitudes and strategies regarding the control of children eating, it means that the parental feeding behaviors consist of cognitive action (attitude) and psychomotor action (strategy) but they only focus on the attitude and strategy regarding parents control in children eating or general atmosphere of emotion in the interaction between parents and children during the meal situation.…”
Section: -33mentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that almost all existing instruments emphasized on parental feeding activities or psychomotor activities that focus on the activities or strategies that parents use to manage how much, when and what children eat such as on parental use of control in feeding. [15][16][17][18] There was a lack of construct involved in cognitive activities that reflected acquiring and gathering information and making judgment and decision. Although Birch, et.al, (2001) and Jansen, et.al., (2012) state that the feeding behaviors of parents are attitudes and strategies regarding the control of children eating, it means that the parental feeding behaviors consist of cognitive action (attitude) and psychomotor action (strategy) but they only focus on the attitude and strategy regarding parents control in children eating or general atmosphere of emotion in the interaction between parents and children during the meal situation.…”
Section: -33mentioning
confidence: 99%
“…The latest study showed that the assessment about the feeding behaviors of parents with toddlers focused only on the dimensions related to food consumption and parental feeding style. [15][16][17][18] Although, the Parents Nutrition Dependent-Care Questionnaire (PNDCQ) seems to have a broader scope of parental feeding behaviors, it was developed for measuring nutrition behaviors that parents performed for their adolescent children. Nutritional needs for toddlers and for adolescents are different, thus, feeding behaviors that parents perform on the behalf of adolescent children are different from those performing for their toddlers.…”
Section: Introductionmentioning
confidence: 99%
“…The present study focuses on a broader range of feeding styles in a sample of low-income African-American infants, drawing on our own previous research and experience in infant feeding (Engle, Bentley, & Pelto, 2000;Ha et al, 2002;Lederman et al, 2004). A comparison of observed and reported feeding styles using qualitative methods provides rich detail on infant feeding styles in this population, within the framework of the parenting style classification proposed by Maccoby and Martin (1983).…”
Section: Introductionmentioning
confidence: 99%
“…With the improbability of new external resources for care being brought to bare on already destitute communities, a 'positive deviance' (PD) approach to care has been raised [105][106][107] and explored. A PD inquiry identifies uncommon, model caretaker and/or household behaviors that result in positive child outcomes in a community [106] .…”
Section: Reforming Caring Attitudes and Practicesmentioning
confidence: 99%
“…One example comes from rural Pakistan, in which newborn care practices from exclusive breastfeeding to thermal protection and hygiene were identified as positive deviant practices and subsequently promoted [106] . Another comes from northern Vietnam, in which the quality of feeding assistance to toddlers was addressed [107] . The program found that affirmative, responsive child feeding, involving verbalization and appropriate encouragement to the children in their second year of life, was the positive behavior resulting in acceptance of food, and improved child nutrition and health status.…”
Section: Reforming Caring Attitudes and Practicesmentioning
confidence: 99%